Temporal and spatial characteristics of submesoscale motions in the Bohai Sea - Si, Xueying; Wang, Tao; Wang, Yanping (Frontiers in Marine Science, 2022)
Submesoscale motions are ubiquitous in the ocean, playing a significant role in energy transfer, mass transport, and biogeochemical processes. However, little attention has been drawn to the submesoscale dynamics in shallow coastal waters. In the present study, submesoscale motions in the Bohai Sea, a typical shallow sea with mean depth of about 18 m, are studied using a validated high-resolution (~ 500 m) model based on Regional Oceanic Modeling System (ROMS). The results show that submesoscale structures in the Bohai Sea are mainly located in the shallow coastal regions, the Bohai Strait, the areas around islands and headlands, and mostly tend to be parallel to the isobaths. The periodic variations of submesoscale motions are closely related to the tidal, spring-neap, and seasonal cycles in the Bohai Sea. The spring-neap variations of submesoscale motions are mainly attributed to the curl of vertical mixing, which is stronger during spring tides than neap tides. Compared with winter, the stronger background horizontal and vertical density variance in summer are conducive to frontogenesis, resulting in more active submesoscale motions. The results in this study are expected to contribute to enriching our knowledge about submesoscale dynamics in shallow coastal seas.